2015
DOI: 10.1097/fjc.0000000000000173
|View full text |Cite
|
Sign up to set email alerts
|

Different Influences of Extracellular and Intracellular Superoxide on Relaxation Through the NO/sGC/cGMP Pathway in Isolated Rat Iliac Arteries

Abstract: Superoxide production is increased in diseased blood vessels, which is considered to lead to impairment of the nitric oxide (NO)/soluble guanylate cyclase (sGC)/cGMP pathway. To investigate the respective influence of extracellular and intracellular superoxide on vascular function through the NO/sGC/cGMP pathway, mechanical responses of rat external iliac arteries without endothelium were studied under exposure to a superoxide-generating agent, pyrogallol, or menadione. Exposure to pyrogallol impaired the rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 40 publications
1
16
1
Order By: Relevance
“…In the previous study, we have shown that superoxide, a precursor of peroxynitrite, has an ability to shift the sGC redox equilibrium toward the NO-insensitive form in isolated endothelium-denuded monkey coronary [22] and rat iliac arteries [21]. Based on this observation, we next examined whether superoxide contributes to the effects of peroxynitrite on the relaxant responses to BAY compounds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the previous study, we have shown that superoxide, a precursor of peroxynitrite, has an ability to shift the sGC redox equilibrium toward the NO-insensitive form in isolated endothelium-denuded monkey coronary [22] and rat iliac arteries [21]. Based on this observation, we next examined whether superoxide contributes to the effects of peroxynitrite on the relaxant responses to BAY compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, these drugs were added to the bathing solution just before exposure to peroxynitrite. The concentration of these drugs was determined based on a previous work [21]. Incidentally, the incubated drugs such as ODQ, peroxynitrite, SOD and tempol were maintained in the bath throughout the experiment.…”
Section: Methodsmentioning
confidence: 99%
“…; Tawa et al. ,b, ,b; Goulopoulou et al. ), two different NO‐independent stimulants acting on sGC were used in this study as valuable tools for indirectly assessing the redox state of the enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…) and iliac arteries (Tawa et al. , ) or in cultured sheep pulmonary artery smooth muscle cells (Zhou et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…BAY 58–2770 (cinaciguat) and HMR-1766 (ataciguat) have been studied in the progression of cardiovascular disease due to their roles as activators of oxidized sGC [8, 9]. Moreover, the therapeutic potency of the sGC activator BAY 60–2770 (4-[[[4-carboxybutyl] [2-[5-fluoro-2-[[4’-[trifluoromethyl] biphenyl-4-yl] methoxy] phenyl] ethyl] amino] methyl] benzoic acid) has been elucidated in nitrate-tolerant arteries [10, 11], obesity [12, 13], platelet activity [14] and asthma [15]. Despite studies investigating the protective role of BAY 60–2770 in coronary artery occlusion [16], few studies have focused on mitochondrial ROS in cardiac IR injury.…”
Section: Introductionmentioning
confidence: 99%